John Stuart Mill about suicide - Álvarez Gálvez, Iñigo (Acta Bioethica, 2016)
John Stuart Mill didn’t take his life; but he could have done it. If he had done it, when he was twenty (as he planned), we would never have known what he thought about it. But he didn’t. And many years later he wrote about nature, God, religion and autonomy. My aim in this article is to show how his thoughts about nature and theism affect in fact his stance about autonomy to commit suicide.